Vegetation type rather than climate modulates the variation in soil enzyme activities and stoichiometry in subalpine forests in the eastern Tibetan Plateau - He, Qingqing; Wu, Yanhong; Bing, Haijian; Zhou, Jun; Wang, Jipeng (Geoderma, 2020)
•Enzyme activity and stoichiometry were studied along a climate and a vegetation type gradient in subalpine forests.•Climate has little impact on the enzyme activity and stoichiometry.•Vegetation type regulated enzyme activities and stoichiometry by affecting plant-associated microbial communities. Soil extracellular enzymes catalyze the rate limiting steps of organic matter decomposition, and enzyme stoichiometry has been used to reflect microbial resource acquisition strategies. However, the patterns and key driving factors of soil enzyme activities and stoichiometry in subalpine forests, which are areas sensitive to global changes, remain unclear. In this study, rhizosphere and bulk soils along two environmental gradients in the subalpine forests of Gongga Mountain, in the eastern Tibetan Plateau, including (1) a horizontal chronosequence with different vegetation types but a similar climate and (2) a vertical elevation gradient with the same vegetation type but different climates, were sampled during the growing and nongrowing seasons. The activities and stoichiometry of soil enzymes related to the microbial acquisition of carbon (C) (β-1,4-glucosidase, BG), nitrogen (N) (β-1,4-N-acetylglucosaminidase, NAG) and phosphorus (P) (acid phosphomonoesterase, AP) were analyzed to reveal their responses to environmental gradients. The results showed that enzyme activities and stoichiometry varied significantly among vegetation types, but were less affected by climate and root proximity. BG activity and ratios of BG to nutrient-acquiring enzymes were significantly higher in broadleaf forests than in coniferous forests. The differences in enzyme stoichiometry between vegetation types were weakly related to the microbial nutrient status (represented by the ratio of soil to microbial element stoichiometry) but might be explained by the higher proportion of ectomycorrhizal fungi in coniferous forests compared to broadleaf forests. The results of this study indicate that vegetation type was a major factor regulating soil enzyme activities and stoichiometry in the subalpine forests, possibly via its influences on plant-associated microbial communities.